KERAGAMAN GENETIK TIGA POPULASI KELAPA SAWIT (Elaeis guineensis Jacq.) TIPE PISIFERA BERDASARKAN MARKA RAPD - Heru Prayogi; Mohammad Basyuni; Lollie AP Putri (Peronema Forestry Science Journal, 2015)
Palm oil producing oil is one of the famous of oil palm plantations as a source of producer non- petroleum oil for Indonesian foreign exchange. Superior varieties of palm oil produced by various research institutions that is tenera originated crossly from dura x pisifera (DxP). Pisifera has an important function in the production of seed of oil palm. Pisifera population is very important to be managed and developed . A RAPD is a method to identify a number of large polymorphism DNA in the genome quickly, efficiently and suitable for the study of genetic diversity. The purpose of this research is to analyze genetic diversity on pisifera type of palm oil by three population namely Yangambi origin, LaMe origin and LaMe silang lanjut in  Bangun Bandar seed productions PT Socfin Indonesia analyzed by RAPD markers. Eighteen  sample for each pisifera population of Yangambi origin, LaMe origin and LaMe silang lanjut showed moderate level of genetic diversity which is shown the average value of 0.24 with the highest was 0,28 and the lowest value was 0.21. The percentage of highest polymorphic on the primer 15 and primer 19 of LaMe origin which reached 100%. The Polymorphic information content (PIC) highest on the primer 11 was on Yangambi origin and primer 10 was laMe silang lanjut of 0.49, while to the lowest PIC on primer 21 of LaMe origin was 0.01.Key words: Palm oil, Elaeis guineensis Jacq., RAPD, genetic diversity